2009
DOI: 10.1002/bem.20547
|View full text |Cite
|
Sign up to set email alerts
|

Millimeter wave effects on electrical responses of the sural nerve in vivo

Abstract: Millimeter wave (MMW, 42.25 GHz)-induced changes in electrical activity of the murine sural nerve were studied in vivo using external electrode recordings. MMW were applied to the receptive field of the sural nerve in the hind paw. We found two types of responses of the sural nerve to MMW exposure. First, MMW exposure at the incident power density >/=45 mW/cm(2) inhibited the spontaneous electrical activity. Exposure with lower intensities (10-30 mW/cm(2)) produced no detectable changes in the firing rate. Sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 41 publications
2
24
0
Order By: Relevance
“…Similar results correlating millimeter wave exposure (62 and 75 GHz) and direct temperature rise were also reported for the changes induced in ionic currents in these neurons [10]. Most recently, the electrical response of an exposed frog sural nerve (>45mW/cm 2 at 42 GHz) showed threshold effects and transient behavior that were not well reproduced by broadband radiant heating [11]. Additional studies have focused on millimeter-wave induced changes in cell membrane permeability.…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…Similar results correlating millimeter wave exposure (62 and 75 GHz) and direct temperature rise were also reported for the changes induced in ionic currents in these neurons [10]. Most recently, the electrical response of an exposed frog sural nerve (>45mW/cm 2 at 42 GHz) showed threshold effects and transient behavior that were not well reproduced by broadband radiant heating [11]. Additional studies have focused on millimeter-wave induced changes in cell membrane permeability.…”
Section: Introductionsupporting
confidence: 71%
“…Civilian Federal Agencies, very few research groups are willing to undertake these studies. Several investigations [4][5][6][7][8][9][10][11][12][13][14][15][16], mainly outside the U.S., have noted significant impact on neuronal activity from modest level millimeter wave exposures (40-130 GHz, 1-100 mW/cm 2 , seconds to minutes) that are not much higher than the Federal Communications Commission-established maximum permissible exposure (MPE) limits of 1 mW/cm 2 for 6 minutes in the 30-300 GHz frequency regime [17]. Synchronization of the firing rate of neurons in the hypothalamus of both rabbit and rat was observed at and below 10 mW/cm 2 [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TRPV2 is a widely expressed calcium channel. In neurons of the peripheral nervous system, TRPV2 is involved in heat sensing and has been proposed as a candidate for the mediation of MMW effects in pain therapy [Alekseev et al, 2010].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was shown that MMW treatment may have an analgesic effect in both human and animal models [Radzievsky et al, 1999;Rojavin et al, 2000]. This hypoalgesia can result from a direct effect of MMW on nerve cells [Radzievsky et al, 2008;Alekseev et al, 2010].…”
Section: Mmw At Intermediate Pd (5-15 Mw/cmmentioning
confidence: 95%